Iron regulatory protein-1 and -2: transcriptome-wide definition of binding mRNAs and shaping of the cellular proteome by iron regulatory proteins - Sanchez, Mayka; Galy, Bruno; Schwanhaeusser, Bjoern; Blake, Jonathon; Bähr-Ivacevic, Tomi; Benes, Vladimir; Selbach, Matthias; Muckenthaler, Martina; Hentze, Matthias W. (Blood, 2011)
Iron regulatory proteins (IRPs) 1 and 2 are RNA-binding proteins that control cellular iron metabolism by binding to conserved RNA motifs called iron-responsive elements (IREs). The currently known IRP-binding mRNAs encode proteins involved in iron uptake, storage, and release as well as heme synthesis. To systematically define the IRE/IRP regulatory network on a transcriptome-wide scale, IRP1/IRE and IRP2/IRE messenger ribonucleoprotein complexes were immunoselected, and the mRNA composition was determined using microarrays. We identify 35 novel mRNAs that bind both IRP1 and IRP2, and we also report for the first time cellular mRNAs with exclusive specificity for IRP1 or IRP2. To further explore cellular iron metabolism at a system-wide level, we undertook proteomic analysis by pulsed stable isotope labeling by amino acids in cell culture in an iron-modulated mouse hepatic cell line and in bone marrow-derived macrophages from IRP1- and IRP2-deficient mice. This work investigates cellular iron metabolism in unprecedented depth and defines a wide network of mRNAs and proteins with iron-dependent regulation, IRP-dependent regulation, or both.
Gesehen am 04.10.2022